2014
DOI: 10.1007/s13277-014-2803-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA-21 as a biomarker for the detection of various carcinomas: an updated meta-analysis based on 36 studies

Abstract: Cancer is a class of diseases with high mortality rate, characterized by unregulated cell growth. Early diagnosis of cancer is currently the most effective method to prevent cancer development and improve the survival rate of patients. Traditional diagnostic methods such as biopsy usually provoke discomfort and unpleasant experience. Recently, microRNAs (miRNAs) were widely reported to be potential biomarkers to detect cancers without invasiveness. MicroRNA-21 (miRNA-21, miR-21) is one of the most prevalent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 50 publications
4
57
0
Order By: Relevance
“…In addition, our metaanalysis showed that both plasma and serum could be recommended as clinical specimens. However, some previous meta-analyses showed plasma-based specimens had a higher accuracy than serum-based specimens, [45][46][47] while others provided opposite tendency, 48,49 further validation tests need to be conducted. 50 We also conducted a subgroup analyses based on the number of miRNAs being profiled.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, our metaanalysis showed that both plasma and serum could be recommended as clinical specimens. However, some previous meta-analyses showed plasma-based specimens had a higher accuracy than serum-based specimens, [45][46][47] while others provided opposite tendency, 48,49 further validation tests need to be conducted. 50 We also conducted a subgroup analyses based on the number of miRNAs being profiled.…”
Section: Discussionmentioning
confidence: 96%
“…Bastaminejad et al [23] reported that miR-21 expression levels in serum were significantly elevated in CRC cases with an 86.05% sensitivity and 72.97% specificity. A meta-analysis that included articles published from 2009 to 2014 where the participants include Caucasians, Asians, and a few Africans showed that circulating miR-21 is useful as an early diagnostic biomarker for several malignant tumors, including CRC [24,25]. Moreover, Sheng et al [26] found that the protein kinase/phosphatase/phosphatidyl-inositol kinase (AKT/PTEN/ PI3K) signaling pathway is intimately linked with many malignant tumors and their progression, drug resistance, immunity, angiogenesis, and metastasis [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of miRNA-21 have been detected in sera and plasma of patients with different malignancies [7].…”
Section: Introductionmentioning
confidence: 99%